2006
DOI: 10.1097/01.fjc.0000200988.85868.f8
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin-Induced Myocardial Noradrenergic Effects in Spontaneously Hypertensive Rats

Abstract: Although increases in myocardial synaptic norepinephrine concentrations contribute toward the progression to heart failure in hypertension, the stimuli for norepinephrine release are unclear. In this study we explored whether neurotensin, a neuropeptide found in heart tissue, could modify myocardial norepinephrine release in spontaneously hypertensive rats (SHR). Prior to the development of cardiac decompensation, baseline coronary effluent norepinephrine concentrations were higher in isolated heart preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This line of thinking receives further support from observations demonstrating that NT effects on blood pressure (Gully et al, 1996;Schaeffer et al, 1997), heart rate (Nisato et al, 1994), myocardial contractility (Nisato et al, 1994;Osadchii et al, 2005aOsadchii et al, , 2006a, cutaneous vascular permeability (Miller et al, 1995), and phosphoinositide turnover in endothelial cells (Schaeffer et al, 1995(Schaeffer et al, , 1998 are dose-dependently inhibited by SR 48692, a specific NT receptor antagonist that exhibits a higher affinity to NTS 1 as compared to NTS 2 receptor subtype (Gully et al, 1993). These findings (briefly summarized in Table 2) therefore support the notion that NT-induced cardiovascular responses are primarily mediated via an activation of the NTS 1 receptor subtype.…”
Section: Nt Receptorsmentioning
confidence: 90%
See 3 more Smart Citations
“…This line of thinking receives further support from observations demonstrating that NT effects on blood pressure (Gully et al, 1996;Schaeffer et al, 1997), heart rate (Nisato et al, 1994), myocardial contractility (Nisato et al, 1994;Osadchii et al, 2005aOsadchii et al, , 2006a, cutaneous vascular permeability (Miller et al, 1995), and phosphoinositide turnover in endothelial cells (Schaeffer et al, 1995(Schaeffer et al, , 1998 are dose-dependently inhibited by SR 48692, a specific NT receptor antagonist that exhibits a higher affinity to NTS 1 as compared to NTS 2 receptor subtype (Gully et al, 1993). These findings (briefly summarized in Table 2) therefore support the notion that NT-induced cardiovascular responses are primarily mediated via an activation of the NTS 1 receptor subtype.…”
Section: Nt Receptorsmentioning
confidence: 90%
“…In contrast, a different pattern of changes in contractile effects of NT has been shown to occur in compensated pressure-overload cardiac hypertrophy (Osadchii et al, 2006a). The maximal ventricular inotropic responses to NT are increased in young spontaneously hypertensive rats as compared to normotensive control WistarKyoto rats, an effect associated with significant enhancement of NT-induced stimulation of the myocardial noradrenaline release (Osadchii et al, 2006a). The putative significance of these changes in the mechanism of cardiac disease remains to be determined.…”
Section: Myocardial Contractilitymentioning
confidence: 93%
See 2 more Smart Citations
“…The authors of this study concluded that down-regulation of NT-induced NE release in the diseased heart may be an important effect to protect the heart against further β-receptor-mediated apoptosis, necrosis, extracellular matrix remodeling, and pump dysfunction [121]. Interestingly though, in another study from the same group, NE release in response to NT was greater from hearts isolated from SHR than the normotensive WKY control [122]. Further, NT increased contractility in the SHR [122].…”
Section: 0 Neurotensin (Nt)mentioning
confidence: 99%